SNX16 activates c‐Myc signaling by inhibiting ubiquitin‐mediated proteasomal degradation of eEF1A2 in colorectal cancer development - Zhiyong Shen; Yongsheng Li; Yuan Fang; Mingdao Lin; Xiaochuang Feng; Zhenkang Li; Yizhi Zhan; Yuechen Liu; Tingyu Mou; Xiaoliang Lan; Yanan Wang; Guoxin Li; et al. (Molecular Oncology, 2020)
Sorting nexin 16 (SNX16), a member of the sorting nexin family, has been implicated in tumor development. However, the function of SNX16 has not yet been investigated in colorectal cancer (CRC). Here, we showed that SNX16 expression was significantly upregulated in CRC tissues compared with normal counterparts. Upregulated mRNA levels of SNX16 predicted poor survival of CRC patients. Functional experiments showed that SNX16 could promote CRC cells growth both in vitro and in vivo. Knockdown of SNX16 induced cell cycle arrest and apoptosis, whereas ectopic overexpression of SNX16 had the opposite effects. Mechanistically, SNX16‐eukaryotic translation elongation factor 1A2 (eEF1A2) interaction could inhibit the degradation and ubiquitination of eEF1A2, followed by activation of downstream c‐Myc signaling. Our study unveiled that the SNX16/eEF1A2/c‐Myc signaling axis could promote colorectal tumorigenesis and SNX16 might potentially serve as a novel biomarker for the diagnosis and an intervention of CRC.